Research and Development of Microphysiological Systems in Japan Supported by the AMED-MPS Project - Ishida, Seiichi (Frontiers in Toxicology, 2021)
Microphysiological systems (MPS) has been actively developed as a new technology for in vitro toxicity test platform in recent years. MPS is a culture technique for the reconstruction of the specific functions of human organs or tissues in a limited space to create miniaturized human test systems. MPS has great promise as a next-generation in vitro toxicity assessment system. Here, I will review the current status of MPS and discuss the requirements that must be met in order for MPS to be implemented in the field of drug discovery, presenting the example of an in vitro cell assay system for drug-induced liver injury, which is the research subject in our laboratory. Projects aimed at the development of MPS have been implemented early in Europe and the United States, and the AMED-MPS project was launched in Japan in 2017. The AMED-MPS project involves industry, government, and academia. Researchers in the field of drug discovery from the pharmaceutical industry participate in the project. Based on the discussions made in the project, I will introduce the requirements to be met by liver-MPS as an in vitro toxicity test platform.